Associations between breastfeeding duration and weight status transitions in early childhood. - Hyojun Park; Eric N Reither (PLoS ONE)
Empirical evidence with respect to the protective effect of breastfeeding on childhood obesity remains inconclusive, and studies on sex-specific associations are sparse. We investigated whether (H1) longer breastfeeding duration reduces the risk of entry into elevated body mass (EBM); and (H2) longer breastfeeding duration increases the likelihood of exit from EBM. Using the Early Childhood Longitudinal Study, Birth Cohort (ECLS-B), our sample comprised 10,550 mother-child pairs after excluding 100 non-biological pairs. The ECLS-B assessed children from 9 months of age through kindergarten, spanning infancy through 7 years of age. We used two transitions in weight status (i.e., entry to EBM and exit from EBM) as outcome variables. The main predictor was breastfeeding duration (i.e., never breastfed, up to 2 months, 3 to 7 months, and 8 months or longer). Multilevel discrete-time models for recurrent transitions were employed to examine bidirectional changes in weight status. Among girls, breastfeeding for 8 months or longer reduced the risk of transitioning into overweight (adjusted Hazard Ratio (AHR): 0.76, 95% CI: 0.64, 0.89) or obesity (AHR: 0.66, 95% CI: 0.53, 0.82). Breastfeeding duration increased the likelihood of exiting EBM in a dose-response fashion among girls. Among boys, breastfeeding for 3 to 7 months was associated with preventing overweight (AHR: 0.79, 95% CI: 0.67, 0.92) or obesity (AHR: 0.82, 95% CI: 0.68, 0.98), but it did not help overcome EBM, regardless of breastfeeding duration. Breastfeeding duration helped to prevent EBM or overcome it, but these effects varied by the child's sex. Further research should elucidate how the benefits of breastfeeding may differ for boys and girls, and explore the potential need for sex-specific public health policies.